THE CONSTITUTIONAL COMPLAINT IN THE POLISH SUPREME LAW – A QUEIXA CONSTITUCIONAL NA LEI FUNDAMENTAL DA POLÔNIA - Szmulik, Bogumil; Poglodek, Andrzej (Espaço Jurídico Journal of Law [EJJL], 2016)
Abstract: The article presents the institution of the constitutional complaint in the 1997 Constitution of the Republic of Poland. For the first time in the history of Polish constitutionalism the current supreme law made it possible for the citizens to directly appeal to the Constitutional Tribunal in order to protect their laws and liberties guaranteed by the supreme law. The article describes the origin of the institution of the constitutional complaint in Europe and in Poland. The main focus, though, is on the extended analysis of the scope and coverage of the constitutional complaint, together with the conditions set by the legislators that must be met for the complaint to be filed. The paper is concluded with the observations on the constitutional regulations and the practice of their applications in the work of the Constitutional Tribunal. Keywords: Constitutional Complaint. Constitutional Tribunal. Human Rights. Constitution Poland.